Kewenanagan Penjabat Kepala Daerah Dalam Mutasi Pegawai: Antara Legalitas Dan Abuse Of Power - Agung Barok Pratama; Aufi Imaduddin; Nabella Maharani Novanta; Mir'atul Firdausi; Shofi Ekiana Putri (Qistie Jurnal Ilmu Hukum, 2026)
The authority of the Acting Regional Head in carrying out the mutation of the State Civil Apparatus (ASN) has caused legal debate due to the difference in regulation between Government Regulation Number 49 of 2008 and the Circular Letter of the Minister of Home Affairs Number 821/5492/SJ. This study aims to analyze the conflict of norms between the two legal instruments and examine the legal implications of the use of discretion by Acting Regional Heads on governance. This study uses a normative juridical method with a legislative approach and a conceptual approach. The legal materials used consist of laws and regulations, legal literature, and relevant research results. The results of the study show that the Circular Letter of the Minister of Home Affairs Number 821/5492/SJ is not in line with the principles of legality and hierarchy of laws and regulations because it provides room for ASN mutation without the mechanism of written approval of the Minister of Home Affairs as stipulated in Government Regulation Number 49 of 2008. This condition has the potential to cause abuse of power, weaken the application of general principles of good governance, and increase the risk of bureaucratic politicization during the transition period of regional leadership. This study concludes that there is a need for more stringent regulatory harmonization and restrictions on the use of discretion by Acting Regional Heads to ensure legal certainty, maintain the neutrality of ASN, and realize good governance.